Financial Literacy and Financial Behavior of College Students in the Digital Era: A Systematic Literature Review - Sutari Sri rejeki; Heni Dwi Listiyaningrum; Feri Lupiana (Denasya Smart Publisher, 2025)
This study synthesizes the findings of five studies related to the influence of financial literacy and financial behavior on students' investment decisions in the digital era. The results of the analysis explain the significant consistency of the influence of financial literacy and financial behavior on students' investment decisions in the digital era. Research Kurniadi and Romadhani & Handinishow that Financial Literacy and Financial Behavior have a significant influence on Investment Decisions. Research Nugraha, Dinarjito Hendri explain the positive influence of Financial Literacy and Financial Behavior on Investment Decisions. The results of the analysis illustrate that the better the financial literacy and behavior possessed by students, the higher the interest in students' investment decisions in the digital era.